Glycemic status and general characteristics among individuals with undiagnosed diabetes; findings from second National Diabetes Survey of Pakistan 2016–2017 (NDSP 08). Issue 6 (June 2022) - Basit, Abdul; Waris, Nazish; Fawwad, Asher; Tahir, Bilal; Siddiqui, Iftikhar Ahmed; ,; Abro, Mujeeb Ur Rehman; Ahmed, Khawaja Ishfaq; Ahmed, Khurshid; Ali, Sobia Sabir; Bilal, Ahmed; Butt, Anam; et al.
Abstract: Background and aim: To observe the glycemic status among individuals with undiagnosed diabetes in urban and rural areas of all four provinces of Pakistan. Methods: The findings of this study are obtained from the second National Diabetes Survey of Pakistan (NDSP) 2016–2017, a nationwide epidemiological survey. Out of 12, 486 individuals approached, 10, 834 participants agreed to be included in the second NDSP. An oral glucose tolerance test was used to assess undiagnosed diabetes individuals according to World Health Organization criteria. Results: The overall weighted prevalence of undiagnosed diabetes was 7.1% (2.4% in urban and 4.7% in rural areas). Based on isolated fasting plasma glucose or 2-h post 75 gm glucose load or combining both, the weighted prevalence of undiagnosed diabetes was 43.5%, 17.6%, and 38.9%, respectively. Out of the 43.5% of individuals, 15.3% had fasting plasma glucose higher than 250 mg/dl at the time of presentation. Among all the individuals, 23.7% were found to be of less than 40 years of age, 29.2% had a positive family history of diabetes, 80.8% were abdominal obese, 53.8% were hypertensive, and 98% were dyslipidemic. In comparison to the elder group, poor glycemic control of ≥10% HbA1c was observed in most of the younger age groups (p < 0.05). Conclusion: A significant number of people remain undiagnosed in this part of the world. The glycemic status along with the other associated risk factors at the time of presentation is alarming. Thus, for the early detection of diabetes, awareness and education in the community are crucial. Hence, long-term complications of diabetes can be prevented. Highlights: The prevalence of undiagnosed diabetes was 7.1%, according to the second National Diabetes Survey of Pakistan 2016–2017. More than 15% of individuals had fasting plasma glucose greater than 250 mg/dl at the time of presentation. The prevalence of undiagnosed diabetes was higher in rural as compared to urban areas. Among all individuals with undiagnosed diabetes, one-quarter of the population were less than 40 years of age.